Nitrogen addition increases microbial necromass in croplands and bacterial necromass in forests: A global meta-analysis. (February 2022) - Hu, Junxi; Huang, Congde; Zhou, Shixing; Liu, Xiong; Dijkstra, Feike A.
Abstract: Increasing anthropogenic nitrogen (N) input has changed the global soil carbon (C) stock, yet the contribution of microbial necromass (amino sugars) to soil C with N addition is poorly understood. Here, we conducted a meta-analysis of 32 publications and evaluated the responses of microbial necromass to N addition. Our results showed that the overall effects of N addition significantly increased the fungal (glucosamine, GluN) and bacterial (muramic acid, MurN; galactosamine, GalN) necromass but did not significantly affect the total microbial necromass (total amino sugars). N addition effects on amino sugars were contingent on ecosystem type. In particular, N addition increased the contents of GluN, MurN, GalN, and total amino sugars in croplands, but in forests N addition only increased the contents of MurN. In croplands, the effects of N addition on microbial necromass depended on whether N was added alone or in combination with phosphorus (P) and potassium (K). Specifically, N addition alone did not significantly affect the contents of bacterial MurN and GalN, fungal GluN, and total amino sugars, while NPK addition significantly increased the contents of all individual ( i.e., GluN, MurN, and GalN) and total amino sugars. In addition, high N addition rates (>150 kg N ha −1 yr −1 ), and long-term N addition (>10 years) significantly increased the contents of all individual and total amino sugars in croplands, possibly because of high N addition rates and long-term N addition may have stimulated microbial growth. Our results demonstrate that N addition increases microbial necromass in croplands and bacterial necromass in forests, providing critical information to improve the sequestration of microbially derived C with continued global anthropogenic N input. Highlights: We used meta-analysis synthesizing N addition effects on microbial necromass (amino sugars). N addition increased all amino sugars and total microbial necromass in croplands. N addition increased only bacterial amino sugars in forests. Long-term N addition, high N addition rates, particularly with P and K, enhanced accumulation of microbial necromass in croplands.